Effect of Synthetic Materials in Reinforcement of Aluminium Matrix Composites - Aluko, Micheal Olalekan; Joseph, Olufunmilayo Oluwabukola (Materials science forum, 2022)
Aluminium matrix composite is a type of innovative technical material that have applications in aerospace, automotive, biotechnology, electronics, and a lot more. Non-metallic reinforcements can be injected into an aluminium alloy to provide advantages over base metal (Al) alloys. Better mechanical properties, improved microstructure, and corrosion resistance are the benefits that have been noticed upon reinforcements. The proportion of reinforcement, kind, size, and forms of aluminium matrix are all important factors in improving mechanical and tribological properties. Investigation in the creation of highly advanced tailored materials using liquid and solid-state processes and the impact it has on the properties and application are the subject of this work. The current research summarizes recent breakthroughs in aluminium-based composites and other particle reinforcement effects. The experiment findings revealed that strengthening the aluminum matrix with reinforcements increased mechanical properties and improves the microstructure. Also, stir casting was seen to be the most popular liquid metal approach because of its cost effectiveness and processing parameters which could easily be adjusted and monitored. It is concluded that aluminum matrix composites have greater mechanical characteristics, microstructure, and corrosion resistance than unreinforced aluminum alloys.